Aging-Associated Cognitive Decline is Reversed by D-Serine Supplementation - Nava-Gómez, L.; Calero-Vargas, I.; Higinio-Rodríguez, F.; Vázquez-Prieto, B.; Olivares-Moreno, R.; Ortiz-Retana, J.; Aranda, P.; Hernández-Chan, N.; Rojas-Piloni, G.; Alcauter, S.; López-Hidalgo, M. (eNeuro, 2022)
Brain aging is a natural process that involves structural and functional changes that lead to cognitive decline, even in healthy subjects. This detriment has been associated with NMDA receptor (NMDAR) hypofunction because of a reduction in the brain levels of D-serine, the endogenous NMDAR co-agonist. However, it is not clear whether D-serine supplementation could be used as an intervention to reduce or reverse age-related brain alterations. In the present work, we aimed to analyze the D-serine effect on aging-associated alterations in cellular and large-scale brain systems that could support cognitive flexibility in rats. We found that D-serine supplementation reverts the age-related decline in cognitive flexibility, frontal dendritic spine density, and partially restored large-scale functional connectivity without inducing nephrotoxicity; instead, D-serine restored the thickness of the renal epithelial cells that were affected by age. Our results suggest that D-serine could be used as a therapeutic target to reverse age-related brain alterations.